Accelerated Monte Carlo Based Simultaneous Dual-isotope SPECT Reconstruction - Karamat, Muhammad Irfan (My University, 2012)
Simultaneous dual-isotope SPECT imaging has a number of applications, for exam- ple, cardiac, brain and cancer imaging. The major concern in simultaneous dual- isotope SPECT is the significant crosstalk contamination between the different isotopes used. The current study focuses on a method of crosstalk compensation between two isotopes in simultaneous dual isotope SPECT acquisition applied to cancer imaging using 99mTc/111In and breast SPECT using 99mTc/123I. Monte Carlo (MC), which is thought to offer the most realistic crosstalk and scatter compensation modelling, in typical implementations, has inherent long calculation times (often several hours or days) associated with it. This makes MC unsuitable for clinical applications. We have previously incorporated convolution based forced detection into SIMIND Monte Carlo (MC) program which have made MC feasible to use in clinical time frames. In order to evaluate the accuracy of our accelerated MC program a number of point source simulation results were compared to experimentally acquired data in terms of spatial resolution and detector sensitivity. We have developed an iterative MC based image reconstruction technique that simulates the photon down-scatter from one isotope into the acquisition window of a second isotope. The MC based estimation of scatter contamination contained in projection views is then used to compensate for the photon contamination during iterative reconstruction. We use a modified ordered subset expectation maximization (OSEM) alogrithm, named as simultaneous ordered subset-expectation maximization (Sim-OSEM), to perform this step. We have undertaken a number of simulation tests and phantom studies to verify this approach in case of both of the dual-isotope combinations (i.e. 99mTc/111In and 99mTc/123I). In breast SPECT studies three different breast sizes were simulated. For each of the breast sizes ten combinations of lesions with 3 lesions per combination, were selected randomly for acquisition and reconstruction of simulation data. The images reconstructed using Sim-OSEM showed crosstalk compensation when compared with images reconstructed using simultaneously (with crosstalk) acquired projection data using analytical attenuation based reconstruction. In case of Sim-OSEM the lesion to background ratios were much closer to actual values compared to images reconstructed for both separately (without crosstalk) and simultaneously (with crosstalk) acquired projection data using analytical attenuation based reconstruction. Activity estimation is also possible with Sim-OSEM and yielded accurate estimates of lesion activities with relatively small error compared to deposited activities. The proposed reconstruction technique also evaluated by reconstruction of experimentally acquired projection phantom data in case of 99mTc/111In. Reconstruction using Sim-OSEM showed very promising results in terms of crosstalk and small angle scatter compensation and uniformity of background compared to analytical attenuation based reconstruction after triple energy window (TEW) based scatter correction of projection data. In our case images obtained using Sim-OSEM showed more uniform background even when compared to the images reconstructed for separately acquired projection data using analytical attenuation based reconstruction may be due to better correction of photons scattered at small angle and got detected under photopeak.
Keywords: Monte Carlo; Dual isotope; SPECT; OSEM; Sim-OSEM; Diagnosis; Medical Biophysics; Nuclear; Other Physical Sciences and Mathematics; Other Physics; Diagnosis